Predictive value of molecular remissions postconsolidation chemotherapy in patients with Core Binding Factor Acute Myeloid Leukemia (CBF‐AML) – a single center analysis‡. Issue 4 (6th September 2016) - Deotare, Uday; Shaheen, Marwan; Brandwein, Joseph M.; Pitcher, Bethany; Kamel‐Reid, Suzanne; Yee, Karen W.L.; Schimmer, Aaron; Minden, Mark D.; Gupta, Vikas; Schuh, Andre C.
Abstract: We analyzed the outcome of 80 sequential patients with core binding factor acute myeloid leukemia and evaluated the influence of molecular monitoring by quantitative reverse transcriptase polymerase chain reaction. With a median follow‐up of 5 years, the estimated 5‐year relapse‐free survival and overall survival were 58% and 66%, respectively. Patients who were in molecular remission at the completion of consolidation chemotherapy had a 21% risk of relapse, while the relapse risk for those in molecular remission at the end of 2 years was 5.5%. Our data indicate that postconsolidation molecular remission does not necessarily preclude disease relapse and further monitoring is required. In contrast, molecular negativity by quantitative reverse transcriptase polymerase chain reaction at the end of 2 years is associated with a low risk of relapse.